Analisis Profitabilitas Usaha Penggemukan Sapi Potong Di Kecamatan Gunungpati Kota Semarang - K. Budiraharjo; M. Handayani; G. Sanyoto (MEDIAGRO, 2011)
This study aims to determine the amount of revenue and profitability levels of fattening beef cattle in Gunungpati District  Semarang City. The research method used is survey method. Data collected include primary and secondary data. Research location in District of Gunungpati Semarang City. The sampling method is random sampling at 4 Livestock Farmers Group, each of Livestock Farmers Group captured 10 members, so that the total sample of 40  respondens. The data obtained are processed in a descriptive qualitative and quantitative. The results showed that the average number of livestock ownership as much as 2.89 ST, the average income of farmers during the six months of maintenance is Rp 1,551,538.-  and the average profitability of 7.76%. Keywords : profit, profitability, beef cattle